A two-year assessment of particulate air pollution and sources in Kuwait. (1st August 2021) - Alahmad, Barrak; Al-Hemoud, Ali; Kang, Choong-Min; Almarri, Fhaid; Kommula, Venkateswarlu; Wolfson, Jack M.; Bernstein, Aaron S.; Garshick, Eric; Schwartz, Joel; Koutrakis, Petros
Abstract: Background: Kuwait and the Gulf region have a desert, hyper-arid and hot climate that makes outdoor air sampling challenging. The region is also affected by intense dust storms. Monitoring challenges from the harsh climate have limited data needed to inform appropriate regulatory actions to address air pollution in the region. Objectives: To compare gravimetric measurements with existing networks that rely on beta-attenuation measurements in a desert climate; determine the annual levels of PM2.5 and PM10 over a two-year period in Kuwait; assess compliance with air quality standards; and identify and quantify PM2.5 sources. Methods: We custom-designed particle samplers that can withstand large quantities of dust without their inlet becoming overloaded. The samplers were placed in two populated residential locations, one in Kuwait City and another near industrial and petrochemical facilities in Ali Sabah Al-Salem (ASAS) to collect PM2.5 and PM10 samples for mass and elemental analysis. We used positive matrix factorization to identify PM2.5 sources and apportion their contributions. Results: We collected 2339 samples during the period October 2017 through October 2019. The beta-attenuation method in measuring PM2.5 consistently exceeded gravimetric measurements, especially during dust events. The annual levels for PM2.5 in Kuwait City and ASAS were 41.6 ± 29.0 and 47.5 ± 27.6 μg/m 3, respectively. Annual PM2.5 levels in Kuwait were nearly four times higher than the U.S. National Ambient Air Quality Standard. Regional pollution was a major contributor to PM2.5 levels in both locations accounting for 44% in Kuwait City and 46% in ASAS. Dust storms and re-suspended road dust were the second and third largest contributors to PM2.5, respectively. Conclusions: The premise that frequent and extreme dust storms make air quality regulation futile is dubious. In this comprehensive particulate pollution analysis, we show that the sizeable regional anthropogenic particulate sources warrant national and regional mitigation strategies to ensure compliance with air quality standards. Graphical abstract: Image 1 Highlights: Beta-attenuation measurements in a desert environment tend to overestimate PM2.5 . Annual PM2.5 levels in Kuwait are nearly four times higher than the U.S. standard. Regional anthropogenic pollution contributes to 44% of PM2.5 in Kuwait City. Dust storms and road dust combined contribute to 37.4% of PM2.5 in Kuwait City. Although dust is ubiquitous, anthropogenic sources are substantial and need to be tackled nationally and regionally.